Hereditary renal cell carcinoma associated with von Hippel–Lindau disease: a description of a Nova Scotia cohort - Bradley, Shannon; Dumas, Nadine; Ludman, Mark; Wood, Lori (Canadian Urological Association Journal, 2013)
Background: von Hippel–Lindau (VHL) disease is an autosomal dominant condition characterized by the development of benign and malignant tumours, including cases of renal cell carcinoma (RCC). Early detection of RCC through routine surveillance can lead to decreased morbidity and mortality. Data on the number of patients in Nova Scotia (NS) who have VHL disease, disease manifestations and the frequency and mode of the surveillance have not previously been collected or reported. This project was designed to obtain that information. Methods: The number and management of patients with VHL disease was determined by multiple sources: the Maritime Medical Genetics Service, patient charts, and pathology, radiology and laboratory data. The actual surveillance being performed was compared with that recommended in the literature. Results: Twenty-one patients from 11 families in NS were identified. Manifestations included cases of RCC (31.6%), central nervous system (CNS) hemangioblastoma (73.7%), retinal hemangioma (47.4%), renal cyst (47.4%) and pheochromocytoma (10.5%). Of the 6 patients with RCC, 4 had bilateral tumours, 2 required kidney transplants and 1 developed metastatic disease. Routine surveillance was being done for the CNS in 62.5% of patients, retina in 47.4%, abdomen in 43.8% and urine catecholamines in only 10.5%. Only 1 of the 6 patients who developed RCC was undergoing routine abdominal imaging. Surveillance investigations were ordered by a number of different specialists. Conclusion: Patients with VHL disease in NS have a number of manifestations associated with their disease, including RCC, in a similar frequency to that reported in the literature. The surveillance of these patients is suboptimal in frequency and coordination. von Hippel–Lindau disease is a complex condition that requires a coordinated approach to care to ensure proper surveillance and treatment. Our study highlights current deficiencies and offers an enormous opportunity for improvement. Généralités : La maladie de von Hippel-Lindau (VHL) est une maladie à transmission autosomique dominante caractérisée par la formation de tumeurs bénignes et malignes, dont l’hypernéphrome. Le dépistage précoce de l’hypernéphrome par des examens réguliers peut amener une réduction de la morbidité et de la mortalité. On ne sait pas combien de personnes sont atteintes de VHL en Nouvelle-Écosse, quelles sont les manifestations de la maladie chez ces patients et quels tests de dépistage sont effectués et à quelle fréquence. Le projet décrit ici visait à obtenir ces renseignements. Méthodologie : Le nombre et la méthode de prise en charge des patients atteints de VHL ont été établis à l’aide de plusieurs sources : la Clinique de génétique médicale des Maritimes, des dossiers de patients, des rapports de pathologie et de radiologie et des analyses de laboratoire. Les méthodes de surveillance mises en place ont été comparées aux méthodes recommandées dans la littérature médicale. Résultats : Vingt et un patients de 11 familles de Nouvelle-Écosse ont été cernés. Les manifestations incluaient : hypernéphrome (31,6 %), hémangioblastomes siégeant au niveau du SNC (73,7 %), hémangiomes rétiniens (47,4 %), kystes rénaux (47,4 %) et phéochromocytomes (10,5 %). Sur les six patients porteurs d’un hypernéphrome, 4 avaient des tumeurs bilatérales, 2 ont eu besoin d’une transplantation rénale et un patient a présenté des métastases. De tous les patients atteints de VHL, 62,5 % ont subi des tests réguliers de dépistage au niveau du SNC, 47,4 %, au niveau de la rétine, 43,8 %, au niveau de l’abdomen, et seulement 10,5 % des patients ont subi des tests réguliers de dépistage des catécholamines urinaires. Sur les 6 cas d’hypernéphrome, un seulement subissait des épreuves régulières d’imagerie au niveau de l’abdomen. Les tests de dépistage avaient été prescrits par différents spécialistes. Conclusion : Les cas de VHL en Nouvelle-Écosse présentent un certain nombre de manifestations liées à cette maladie, dont l’hypernéphrome, à une fréquence proche de celle mentionnée dans la littérature. La fréquence et la coordination des épreuves de dépistage sont sous-optimales. La maladie de VHL est une affection complexe nécessitant une bonne coordination des soins afin d’assurer une surveillance et un traitement adéquats. Cette étude montre les lacunes actuelles et pointe vers des améliorations substantielles.